Connection among Body Measurements and Flying Speed of Racing Pigeon† - Steven Mercieca; Bertalan Jilly; András Gáspárdy (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
The ability of racing pigeons to navigate and to find their way home is determined by many factors. The aim of this investigation was to prove the outer and inner environmental impacts on the flying performances of racing pigeon flock. The fieldwork consisted of taking down of various body measurements of 49 birds,  which was improved by collection of racing-, meteorological-, geographical-, and pedigree data. According to the age corrected body measurements the birds of actual flock were longer in wing length, narrower in wing width and lighter in body weight than birds in Horn's study. The breeding value for flying speed (BV speed) was calculated by an individual animal model taking the proven environmental effects (fixed: year of race, wind direction, rain fall, reproductive status; covariates: distance, temperature-humidity index) into consideration next to the genetic relatedness. The BV speed showed significant association with the real flying speed only (r=0.71), and there were no statistically proven correlations with the body measurements and the body condition loss as well. While the wing length stayed in a closer negative connection (r=-0.40, p<0.05) to the loss in body condition. Association of traits was further evaluated by use of factor analysis, from which it is concluded that the measurement responsible for body capacity, the measurements contributing the wing surface area, and the speed of bird are belonging to different determining groups (factors). Over and above, from the investigation it can be concluded that the flying speed of the racing pigeon is not  clearly determined by their body measurements, by their live weights and condition losses. However, the contribution of the body weight, chest depth (as breast muscle volume), and wing length to the flying success is strongly imaginable, which needs further research